(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Introduction: This study was conducted to know the effect of adding wormwood extract to drinking water and comparing it with the antibiotic tylosin on some immune and biochemical characteristics of broiler chickens. Methods: 525 broiler chickens of the Rose 308 strain used in this experiment, divided into 6 treatments with 3 replicates for each treatment. The treatments were as follows: (T1) drinking water without addition (control treatment), (T2), (T3) 0.25, 0.50 gm tylosin / liter of water. (T4), (T5), (T6) 0.25, 0.50, 1 ml wormwood extract / liter of water. Some blood biochemical parameters were measured like total protein, glucose, cholesterol, triglycerides and immune parameters to determine the amount of antibodies against Newcastle disease, Gumboro, infectious bronchitis and influenza in broiler chickens. Results: The results showed no significant differences in the percentage of glucose and triglycerides, while there significant differences (P≤0.01) in the percentage of cholesterol and total protein, in which the wormwood treatments were superior compared to the tylosin treatments and control. In the immune characteristics, there significant differences (P≤0.01) in the size of antibodies directed against Newcastle disease and influenza, in favor of the tylosin treatments compared to the wormwood treatments, while for gumboro and infectious bronchitis, there were no significant differences. Conclusion: The aqueous extract of wormwood gave a similar effect to the antibiotic tylosin with regard to the biochemical characteristics of blood, there was no significant difference between the treatments with regard to antibodies directed against the Newcastle, gumboro , infectious bronchitis and influenza.